Sistem Informasi Klasifikasi Atlet Ju-Jitsu Berbasis Web Menggunakan Metode Agile - Kharisma Dinda Amareta; Zunita Wulansari; Udkhiati Mawwadah (Fakultas Teknik Universitas Hamzanwadi, 2026)
The development of information technology has increased the need for efficient and accurate athlete data management systems. In Ju-Jitsu, the athlete classification process is still performed manually, making it prone to errors and time-consuming. This study develops a web-based Ju-Jitsu athlete classification system capable of automatically grouping athletes based on weight, gender, and age in accordance with official competition regulations. The system was developed using the Agile method, with React.js for the frontend and Node.js with Express.js for the backend. Classification rules were implemented in a structured manner to ensure consistent calculations and reduce manual errors. System testing using Black Box Testing achieved a 100% success rate, while expert validation produced scores of 3.55 in the first iteration and 3.7 in the second iteration, indicating that the system functions properly and is feasible for use. The system effectively improves the accuracy, consistency, and efficiency of the athlete classification process and supports better data management during competitions